Dantigerous cyst in dentistry. Case report - Luís José Floriam,; Marcelle Danelon; Vlamir Oliveira da Silva,; Nayara Gonçalves Emerenciano; Liliana Carolina Báez-Quintero; elsa Deise Macchetti Kanaan (Revista de Odontopediatria Latinoamericana)
The dentigerous cyst is defined as a cystic lesion involving the crown of an included tooth, which is attached to the cement enamel junction. Clinically it is manifested by asymptomatic increase in volume, and is usually discovered by routine radiographic examination or by investigation of non-erupted tooth. Radiographically, it presents as a unilocular radiolucent lesion around an even tooth. This study presents a clinical case of a patient with a dentigerous cyst in the posterior region of the mandible, treated surgically by enucleation and exodontia of involved teeth. A 9-year-old male patient attended the Pediatric Dentistry Clinic of the University of Ribeirão Preto (UNAERP), Brazil, complaining of lower left bulging of the face, with marked facial asymmetry, whose panoramic radiographic examination and computed tomography evidenced the presence of large dentigerous cyst. In view of the clinical and radiographic findings, the treatment plan was to enucleate the cyst to allow eruption of the permanent successors, followed by the exodontia of the dental elements 74/75. Surgical treatment was fast and resolute, showing that the choice of treatment should be carefully weighted for each case.